Gestión técnica de factores de riesgos físicos con potencial de accidentes del trabajo y enfermedades profesionales en el G.A.D. de la provincia de Cotopaxi, 2015: manual de procedimiento de seguridad para riesgos físicos. - Silva Frey, Fabián (2015)
Phases of the technical management of risks of physical factors and control measures are applied. Which, in Chapter 1 determines the theoretical framework that will serve as a general reference to comply with the technical management raised, based on the legislation of our country as well as the appropriate international standards have been selected. In Chapter 2, are established methodologies for: apply hazard identification matrix, surveys and how to measure physical risk factors; also describes the methodology for the evaluation of risk factors physical, through the recommendations of the Ministry of labour. Chapter 3 sets out the results achieved in each of the areas and jobs, with the implementation of surveys with a sample of all the staff, as well as also applying hazard identification matrix physical factors were mainly found as: noise, poor lighting, high or low temperatures, vibrations and non-ionizing radiation, humidity, and ventilation; then these factors were measured to determine criticality with calibrated equipment’s as: sound level meter, light meter, meter of thermal stress and vibration meter; Finally assesses risk factors determining criticality and establish the measures of control for the most significant risk factors that can lead to accidents at work or occupational diseases. Chapter 4, proposes a Manual of safety procedures for the risks evaluated, physical the procedures cover assessed risk factors, for which the Guide for the development of security procedures was applied. Finally, the conclusions and recommendations of application are set to keep the G.A.D. in Cotopaxi province, the technical management.